Perbandingan Kinerja Sistem Perkuatan Tanah Pada Penanganan Lereng Tidak Stabil Di Proyek Jalan Tol - Bimawijaya Laia; Jun Fajar Krisman Giawa; Kevin Berkat Mendrofa; Andrew Christover Harefa; Laurensius Tema Berkati Jaya Gulo (CV. SINAR HOWUHOWU, 2025)
This study presents a comparative analysis of the technical effectiveness and cost efficiency of three ground reinforcement methods—geogrids, soil nailing, and gabion retaining walls—for slope stabilization in highway construction projects. Numerical modeling using geotechnical software was conducted to evaluate the performance of each method based on the increase in the factor of safety (FS) and the degree of slope deformation. The results indicate that soil nailing is the most technically effective method, providing the highest FS increase (up to 1.68) and the best control over deformation. However, it also incurs the highest implementation cost. In contrast, geogrids proved to be the most cost-efficient solution, although with a more moderate FS increase. Meanwhile, gabion retaining walls offer a good compromise between performance and cost. The study concludes that the optimal choice of a ground reinforcement method must be based on a multi-criteria analysis that considers specific geotechnical conditions, safety priorities, and budget availability. The findings of this research are expected to serve as a practical guide for engineers in designing safe, efficient, and sustainable slope stabilization solutions.